2013
DOI: 10.1016/j.jvs.2013.06.068
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of intentional occlusion of accessory renal arteries during endovascular aortic aneurysm repair

Abstract: Intentional ARA occlusion during EVAR was not associated with changes in renal function or blood pressure measurements, even when performed in patients with more advanced renal dysfunction. Type II endoleak may result from persistent outflow into large (>3 mm) ARAs that arise from the aneurysm sac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 23 publications
2
60
1
Order By: Relevance
“…Previous studies documented that the coverage of ARAs by endografts can be well tolerated in the short-and medium-term without significant impairment of renal function or deterioration of hypertension. [5][6][7][8][9][10][11] In contrast, Greenberg et al 10 reported that postoperative renal infarction was detected in 84% of patients after EVAR with ARA coverage, and that the mean volume of the infarcted area was 12% of the total renal volume, indicating a certain degree of ischemic damage to the kidney parenchyma. Malgor et al 11 reported that coverage of ARAs larger than 3 mm in diameter during EVAR could result in type II endoleak leading to aneurysm enlargement.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies documented that the coverage of ARAs by endografts can be well tolerated in the short-and medium-term without significant impairment of renal function or deterioration of hypertension. [5][6][7][8][9][10][11] In contrast, Greenberg et al 10 reported that postoperative renal infarction was detected in 84% of patients after EVAR with ARA coverage, and that the mean volume of the infarcted area was 12% of the total renal volume, indicating a certain degree of ischemic damage to the kidney parenchyma. Malgor et al 11 reported that coverage of ARAs larger than 3 mm in diameter during EVAR could result in type II endoleak leading to aneurysm enlargement.…”
Section: Discussionmentioning
confidence: 98%
“…However, more recent studies report a mild decline in postoperative renal function of patients with covered accessory renal artery after EVAR (26). In addition, coverage of larger (>3 mm) accessory renal artery has been associated with an increased risk of type II endoleak (27).…”
Section: Renal Arterymentioning
confidence: 99%
“…However, in unique instances, intraoperative variables may also influence whether a Type II endoleak occurs in the postoperative period. Ward et al demonstrated that prophylactic embolization of a patent inferior mesenteric artery and/or lumbar arteries decreases the risk of a large persistent Type II endoleak [20]. On the other hand, in repairs that involve distal endograft fixation in the external iliac artery, an inadequate embolization and/or plugging of an internal iliac artery can lead to a persistent retrograde Type II endoleak from the branch vessel and into the aortic sac-particularly if the ipsilateral common and internal iliac arteries are also aneurysmal.…”
Section: Intraoperative Predictors Of Type II Endoleak Developmentmentioning
confidence: 99%
“…Treatment of Type II endoleaks by way of prevention is cited in various reports [19,20,25]. This is theoretically achieved with prophylactic embolization of arterial branches and collaterals that may ultimately lead to a Type II endoleak following EVAR.…”
Section: Treatment Of Type II Endoleaksmentioning
confidence: 99%
See 1 more Smart Citation